Economic freedom, inequality and growth - Ismail, Norhazlin; Law, Siong Hook (School of Social Sciences, Universiti Sains Malaysia, 2012)
The importance and impact of economic freedom and income inequality on economic growth has been extensively investigated. Income inequality itself is a problem that needs to be addressed. Yet, the dilemma whether economic freedom and income inequality actually help to explain the corresponding differences in and across countries economic growth rates are still in debate. Thus, the aims of this study were to examine the link between income inequality and economic growth, and to determine the effect of economic freedom on economic growth. Data were gathered from 44 developing countries from year 1976 to 2005 and analysed using a dynamic panel GMM estimation technique. Besides, the economic freedom, income inequality and economic growth data, data on institutional, investment, population and human capital are added to control variation in economic growth. It is argued that there are interactions between economic freedom, income inequality and economic growth. The empirical results reveal that economic freedom and income inequality are statistically significant determinants of economic growth. Improvement in both economic freedom and income equality lead to economic growth. Increasing the economic growth had been the centre of economic policymaking in many countries around the globe. As such, the issues presented in this study would serve as important guidelines towards understanding the influence of the economic variables and provides a platform for debate on the experiences of developing countries in increasing the economic growth in their countries.